Pengaruh Literasi Keuangan terhadap Keputusan Investasi Mahasiswa Banten - Evi Silvia Aulina; Lala Puspita Sari; Siti Aliyah; Hadi Peristiwo; Wahyu Hidayat (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Students are a group of people who are vulnerable to the temptation of a consumer lifestyle. Therefore, adequate financial knowledge is required to take appropriate investment decisions. The aim of this research is to analyze the influence of financial literacy on student investment decisions in Banten Province. This research uses quantitative methods with questionnaire data collection techniques. Data were analyzed using multiple regression. The findings show that financial literacy has a positive and significant effect on student investment decisions in Banten Province. These results indicate that financial literacy is an important factor that needs to be considered in efforts to increase student investment participation. Based on this research, there is a need for ongoing financial literacy training and outreach to Banten students to increase their knowledge and understanding of investment so that they can make smarter and more profitable investment decisions.